Addressing SARS-CoV-2 evolution: neutralization of emerging variants of concern by the AVX/COVID-12 ‘Patria’ vaccine based on HexaPro-S ancestral Wuhan spike or its updated BA.2.75.2 version - Carballo-Uicab, Gregorio; Mellado-Sánchez, Gabriela; González-González, Edith; Salinas-Trujano, Juana; Mendoza-Salazar, Ivette; López-Olvera, Karina; Gómez-Castellano, Keyla M.; Salazar, Ma. Isabel; Torres-Flores, Jesús M.; Chagoya-Cortés, Héctor Elías; Paz-De la Rosa, Georgina; Mena, Ignacio; et al. (Frontiers in Immunology, 2025)
IntroductionSevere acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains a global health challenge, causing severe morbidity and mortality, particularly in vulnerable groups such as the elderly, immunocompromised individuals, and those with comorbidities. In low- and middle-income countries (LMICs), vaccine access is hindered by high costs and inequitable distribution. To tackle these issues, Mexico developed the AVX/COVID-12 (V-Wu) vaccine, a recombinant Newcastle disease virus (NDV)-based platform expressing a stabilized ancestral Wuhan spike protein (HexaPro-S). Locally manufactured after rigorous testing and regulatory approval, V-Wu aims to enhance self-sufficiency and equity in immunization. MethodsThis study evaluates an updated vaccine version, AVX/COVID-12 (V-BA), designed to combat Omicron subvariants by expressing the HexaPro-S protein of BA.2.75.2. Both vaccines were administered intramuscularly in K18-hACE2 transgenic and BALB/c mouse models using a prime-boost regimen. Immunogenicity was analyzed by measuring antibodies against Omicron S proteins BA.2.75.2 and XBB.1.5, as well as neutralizing antibodies against Wuhan, BA.1, XBB.1.16, and JN.1 variants. ResultsBoth vaccines were safe, eliciting robust antibody responses against Omicron S proteins and neutralizing antibodies against multiple emerging SARS-CoV-2 variants of concern (VOCs). V-BA demonstrated superior protection against current Omicron variants, while V-Wu offered broader coverage, including the ancestral Wuhan strain and emerging variants like JN.1. DiscussionThese findings underscore the adaptability of NDV-based platforms in addressing the evolving SARS-CoV-2 landscape and reaffirm the ongoing utility of the ancestral Patria vaccine. Together, they demonstrate the potential of these platforms to drive the development of next-generation vaccines tailored to emerging viral threats, contributing to global health equity.